Development of Tetra-primer ARMS PCR based genotyping method for A clinically important SNP CYP2C19*3 (rs4986893) - Rahman, Wasifa Ar (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2020.